Dental Bleachıng Treatment: A Case Report - Osman Gökay (European Annals of Dental Sciences, 2017)
In cosmetic dentistry, vital tooth bleaching with gel techniques has been very popular. It involves home and office bleaching techniques. At home bleaching, generally, a soft private plastic tray filled with a commercially carbamide peroxide CP gel is used by the patient. Studies showed significant shade or color improvement following at-home use of the CP. In-office bleaching, higher concentration of CP or hydrogen peroxide HP is applied to tooth surface under the dentist’s supervision. It provides faster results compared with home bleaching systems. However, when the two gel techniques were combined, whiter teeth could be obtained. The 25-year-old man was dissatisfied with the brighter ceramic bridges and crowns than his own teeth, which he had done two months ago in a dentist. There were two options; either all of the fixed prothesis will be renewed or bleaching treatment will be applied to his own teeth. Replace the prothesis is more expensive and time consuming. In addition, dental tissue may be damaged during this procedure. Later was chosen and the combined bleaching home+office was used in this case. Patient did not suffer from local complications of teeth and irritation of gums during bleaching. After bleaching treatment, dental hypersensitivity was minimal. The patient was satisfied with the results of the bleaching.